2022
DOI: 10.7759/cureus.31433
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Access to Abortion and Mental Health in Women of Childbearing Age: Analyses of Data From the Global Burden of Disease Studies

Abstract: Background It has often been suggested that restricting access to legal abortion could have a negative impact on the mental health of women seeking this procedure. The recent judgment of the United States Supreme Court in the Dobbs case has brought the question of the psychological impact of changes in abortion policy into focus. The results of studies on the link between induced abortion and mental health are contradictory, and interpreting the results of these studies is complex due to a multitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…[16] Individual beliefs, emotions, and circumstances, including feeling anger, wonder, and frustration, are behaviours commonly expressed by women post ToP and has an impact of selfdistractive behaviours as part of negative QoL in long run. [17] In addition to feelings of fear and anxiety, a finding related to a study of depression symptoms that interfere with QoL is consistent with this study. [18] The literature suggests that the impact of depressive behaviour may be different from that of anxiety, [8] indicating that anxiety and depression should be treated as separate conditions rather than being combined; and that depression should be given a greater weighting when both are present.…”
Section: Mixed Feelings and Uncertaintysupporting
confidence: 90%
See 1 more Smart Citation
“…[16] Individual beliefs, emotions, and circumstances, including feeling anger, wonder, and frustration, are behaviours commonly expressed by women post ToP and has an impact of selfdistractive behaviours as part of negative QoL in long run. [17] In addition to feelings of fear and anxiety, a finding related to a study of depression symptoms that interfere with QoL is consistent with this study. [18] The literature suggests that the impact of depressive behaviour may be different from that of anxiety, [8] indicating that anxiety and depression should be treated as separate conditions rather than being combined; and that depression should be given a greater weighting when both are present.…”
Section: Mixed Feelings and Uncertaintysupporting
confidence: 90%
“…Comparing these themes with the literature, we note that our findings are similar to those of various studies. [17][18] Additionally, our findings from the FGDs highlighted how these attributes could be differentiated by positivity, negativity, and what could be done better to improve positive mental and physical health outcomes. On this note, those with distressing difficulties (at the time of the FGDs) were more likely to talk about losses (what would reduce QoL), whereas those with improved mental health spoke more of the things that would add to QoL.…”
Section: Discussionmentioning
confidence: 92%
“…The risk of developing depression is higher in certain periods of a woman's life, such as pregnancy ( 4 ) and menopause ( 4 ). In particular, during pregnancy, many relevant physiological, hormonal, social and psychological changes occur ( 5 ), which can explain why a significant proportion of pregnant women experience depressive and comorbid anxiety symptoms ( 6 , 7 ). Recent reviews have reported that from 15 to 65% of women experience depressive symptoms during pregnancy, mainly characterized by depressed mood, low self-esteem, loss of appetite, feelings of fatigue and poor concentration ( 8 ).…”
Section: Introductionmentioning
confidence: 99%